Development of Oxide-Type Cathode Materials towards Room-Temperature Magnesium Rechargeable Batteries - Hiroaki KOBAYASHI (Electrochemistry)
Magnesium rechargeable batteries (MRBs) are ones of promising low-cost, safe, and high-energy post-lithium-ion batteries. However, critical issues still lie both in electrolytes and cathodes, despite 20 years since the first report of prototype MRB. Difficulty in the utilization of high-energy oxide-type cathode materials derives from their low ion-diffusion and electrical conductivity, leading to low reversible capacity. Herein, various nanotechnologies for spinel oxide cathode materials and cathode/electrolyte interface are displayed to operate the MRB, even at room temperature conditions. Surface-modified ultraporous spinel nanoparticles exhibit electrochemical magnesium intercalation, achieving the theoretical capacity. In addition, the decomposition reaction of the ether-based electrolyte at the highly reactive cathode surface is suppressed by the Mg2+-conductive coating layer. These cathode material designs will open up new technologies for the practical application of room-temperature MRB.